SAFETY OF ROAD TRANSPORT SYSTEM AND ROAD SAFETY PROGRAMMES IN THE CZECH REPUBLIC - Kozlovsky, Jiri; Drahotsky, Ivo (Doprava a spoje, 2012)
The paper deals with the safety of road transport system. It evaluates traffic safety on roads in the Czech Republic and abroad. The paper gives several examples of past and present road safety programmes including their brief descriptions.